Basothorhynchus, a new Oosomini genus from the highland plateau of Lesotho (Coleoptera: Curculionidae: Entiminae) - Borovec, Roman (Zootaxa, 2019)
A new genus, Basothorhynchus gen. n. (Coleoptera: Curculionidae: Entiminae: Oosomini) is described with one new species from Lesotho, Basothorhynchus endroedyi sp. n. The new genus is well defined by its small glabrous body, the rostrum continuous with the head, all femora with a distinct tooth, the tibiae abruptly enlarged on the inside, the metatibiae lacking a corbel and the free claws.